A Closer Look at the Yardstick: A New Discount Rate Measure with Precision and Range†. (14th July 2015) - Yoon, Haewon; Chapman, Gretchen B.
Abstract: In intertemporal choice research, choice tasks (i.e., choosing between 80 today and 100 in a year) are often used to elicit a discount rate. The discount rate derived from a choice task, however, is largely restricted by the granularities and ranges of the questions asked. We examined this restriction in three popular discount rate measurements using simulations and experiments, and we propose an alternative procedure (Three‐option Adaptive Discount rate measure (ToAD)), which is capable of measuring a wide range of discount rates (from approximately .035% to 350 000% annual percentage rate) with high precision using 10 questions, in under a minute. ToAD can be easily implemented in online surveys (i.e., Qualtrics). Copyright © 2015 John Wiley & Sons, Ltd.